Facilitators and barriers to physical activity following pulmonary rehabilitation in COPD: a systematic review of qualitative studies - Robinson, H; Williams, V; Curtis, F; Bridle, C; Jones, A (Springer Nature, 2018)
Pulmonary rehabilitation has short-term benefits on dyspnea, exercise capacity and quality of life in COPD, but evidence suggests these do not always translate to increased daily physical activity on a patient level. This is attributed to a limited understanding of the determinants of physical activity maintenance following pulmonary rehabilitation. This systematic review of qualitative research was conducted to understand COPD patients’ perceived facilitators and barriers to physical activity following pulmonary rehabilitation. Electronic databases of published data, non-published data, and trial registers were searched to identify qualitative studies (interviews, focus groups) reporting the facilitators and barriers to physical activity following pulmonary rehabilitation for people with COPD. Thematic synthesis of qualitative data was adopted involving line-by-line coding of the findings of the included studies, development of descriptive themes, and generation of analytical themes. Fourteen studies including 167 COPD patients met the inclusion criteria. Seven sub-themes were identified as influential to physical activity following pulmonary rehabilitation. These included: intentions, self-efficacy, feedback of capabilities and improvements, relationship with health care professionals, peer interaction, opportunities following pulmonary rehabilitation and routine. These encapsulated the facilitators and barriers to physical activity following pulmonary rehabilitation and were identified as sub-themes within the three analytical themes, which were beliefs, social support, and the environment. The findings highlight the challenge of promoting physical activity following pulmonary rehabilitation in COPD and provide complementary evidence to aid evaluations of interventions already attempted in this area, but also adds insight into future development of interventions targeting physical activity maintenance in COPD.